THE THEORETICAL AND PRACTICAL ASPECT OF SELECTING THE CAPITAL BUDGETING METHODS - Tamar Gamsakhurdia; Ketevan Maisuradze (European Scientific Journal, ESJ, 2016)
This paper reports the results of a survey with respect to the current practice of capital budgeting techniques in the countries with different levels of economic development. The choice of capital budgeting methods used by companies show that the main reason for the use of the NPV was its superiority as it accurately takes into account the time value of money. The IRR method is used owing to its ability to rank projects and to indicate the actual return of each project, thereby informing managers whether an investment will increase the company’s value. The results indicated that the continual use of PB was based on the simplicity of the technique. Financial managers should utilize multiple tools in the capital budgeting process; these results reflect a better alignment of views between academia and business.